Performance Test Application Center For Research And Community Service With The Pieces Method At STKIP Dharma Bakti Lubuk Alung Foundation - Dodi Nofri Yoliadi (Jurnal Ilmu Komputer, 2023)
The Center for Research and Community Service is a unit that manages the fields of research and community service. So far, the Center for Research and Community Service (P3M) at the Dhar-ma Bakti Lubuk Alung Foundation STKIP manages data on research activities and community service using Microsoft Access, which is entered into the database. Therefore, a web-based research and community service center application for the Dharma Bakti Lubuk Alung Foundation was built using the PHP programming language and database processing using MySQL. The application development method used is the waterfall method. GTMe-trix will be used as software testing to evaluate the performance of this application. The method used in this study is a quantitative method with the PIECES analysis model. The application performance evaluation Center for Research and Community Service received a grade A, indicating that the application was running "very well" based on the results obtained from all pages tested using GTMetrix. The results of the analysis of the level of satisfaction of users of the Center for Research and Community Service applications obtained a value of 4.4, which means that the level of user satisfaction can be categorized as "very satisfied."